The Archaeology of Afghanistan from Earliest Times to the Timurid Period - Allchin, F. R. (1978)
Chapter 3, J.G.Shaffer, The Later Prehistoric Periods. Ch. 4, D. W. MacDowall — M. Taddei, The Early Historic Period: Achaemenids and Greeks.